Analysis of IKM Perceptions on The Role of Events to Moderate the Influence of Product Quality and Product Value on Brand Image (Study on Denpasar Festival) - Ida Ayu Putri Ratna Dewi; I Ketut Setia Sapta; Putu Kepramareni (AIBPM Publisher, 2021)
The development of the Creative Economy sector in collaboration with the IKM Sector to maintain local culture so it continues to grow and be sustainable. The development of IKM creativity is facilitated by the Denpasar City Government through the Denpasar Festival which is expected to be able to build an ecosystem, brand image and creative economy networking. For this reason, event implementation as one of the promotional media, so that the IKM brand image can be known by the wider community, both domestically and abroad. The purpose of this study is to examine and analyze the effect of product quality and product value on the brand image of IKM and moderated by the event. Respondents in this study were IKM who participated in the Denpasar Festival event for 3 consecutive years (2017 to 2019). The number of respondents used was 154 IKM using a sampling technique called Proportionate Stratified Random Sampling. This research used SEM analysis with SmartPLS 3.0 program. The results showed that product quality has a positive and significant effect on brand image, product value has no effect on brand image, events can moderate the effect of product quality on brand image, and events are not able to moderate the effect of product value on brand image.